PRESENT TO THE LIMITS: Transmedia strategies by female artists in contemporary art and within the KobieTY/woMEn collection - Miaskowska, Marta (Design/Arts/Culture, 2025)
The work of women artists with their own image, situated against the background of the development of new media art and feminist contexts, reveals an area of ​​reflection on creative responsibility, which is manifested by persistent presence. The perspective of a lens, often replacing a mirror, or cultural customs attributed to women, such as makeup, becomes a cliché through which subsequent artists shed new light using various new media. The combination of performative and on-camera activities in women's work has its own separate dimension in art, and its features are reflected in the works presented at the kobieTY/woMEn exhibition, to which this text refers. The long-term strategy of standing in front of the lens, i.e. in front of oneself and the audience, becomes an act of confronting contemporary issues. Filtering them through herself extends private experiences into the public sphere, making her visual presence an element of the broadly understood regaining women's identity.